2009
DOI: 10.1111/j.1095-8649.2009.02468.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestive capacities, inbreeding and growth capacities in juvenile Arctic charr Salvelinus alpinus

Abstract: Genetic variation in growth performance was estimated in 26 families from two commercial strains of Arctic charr Salvelinus alpinus. Physiological determinants of growth and metabolic capacities were also assessed through enzymatic assays. A relatedness coefficient was attributed to each family using parental genotypes at seven microsatellite loci. After 15 months of growth, faster growing families had significantly lower relatedness coefficients than slower growing families, suggesting their value as indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…In addition to the area available for nutrient absorption, enzyme activities are expected to influence the efficiency with which nutrients are digested and absorbed, and be linked to feed utilization and growth. For example, there is some evidence for a link between protease activity and growth in salmonids and some other fish species [25,[56][57][58][59][60]. In our study, the low enzyme activities recorded at 875 and 2090 ddPSF (Fig 9) coincided with periods of reduced fish growth (low TGC), including the time of photoperiod manipulation used to induce parr-smolt transformation.…”
Section: Plos Onesupporting
confidence: 58%
See 2 more Smart Citations
“…In addition to the area available for nutrient absorption, enzyme activities are expected to influence the efficiency with which nutrients are digested and absorbed, and be linked to feed utilization and growth. For example, there is some evidence for a link between protease activity and growth in salmonids and some other fish species [25,[56][57][58][59][60]. In our study, the low enzyme activities recorded at 875 and 2090 ddPSF (Fig 9) coincided with periods of reduced fish growth (low TGC), including the time of photoperiod manipulation used to induce parr-smolt transformation.…”
Section: Plos Onesupporting
confidence: 58%
“…For example, tryptic activity was much lower at 2090 ddPSF than at the preceding and subsequent sampling times, but chymotrypsin did not show an equivalent trough (Fig 9). A lack of concordance between the activities of trypsin and chymotrypsin has been reported in previous studies in which fish have been provided with feeds differing in nutrient composition, or held under conditions that have induced differences in feed intake and growth [34,35,57,58,62,78]. Although the reasons for the differences in the patterns of the enzymatic activities of trypsin and chymotrypsin remain unclear they have been linked to differences in growth trajectories and feed conversion observed in fish held under different conditions [24,57,61,63].…”
Section: Plos Onementioning
confidence: 87%
See 1 more Smart Citation
“…They found that the two strains had significantly different allelic and genotypic distribution and that the genetic variability was lower in the Quebec domesticated strains than in wild populations of the same species. In a later study (Ditlecadet et al 2009) with the same farmed strains, it was found that faster-growing families had significantly lower relatedness coefficients than slower-growing families. Recently, Nugent et al (2017) presented a single nucleotide polymorphism (SNP) linkage map for Arctic charr based on genetic sequencing of 85 full-siblings, and their parents, from the Fraser strain.…”
Section: Farming Of Arctic Charrmentioning
confidence: 87%
“…In Canada, the potential for selective breeding in several strains has been investigated (Ditlecadet et al 2006(Ditlecadet et al , 2009Blackie et al 2011;Norman et al 2011Norman et al , 2014. Two natural populations from geographically distant locations and phylogenetic lineages have been the primary contributors to the Arctic charr being produced in the Canadian industry (Blackie et al 2011): the Nauyuk Lake system in Nunavut and the Fraser River in Labrador.…”
Section: Farming Of Arctic Charrmentioning
confidence: 99%